Bridge-Enhanced Anterior Cruciate Ligament Repair Is Not Inferior to Autograft Anterior Cruciate Ligament Reconstruction at 2 Years: Results of a Prospective Randomized Clinical Trial. Issue 6 (May 2020) - Murray, Martha M.; Fleming, Braden C.; Badger, Gary J.; Freiberger, Christina; Henderson, Rachael; Barnett, Samuel; Kiapour, Ata; Ecklund, Kirsten; Proffen, Benedikt; Sant, Nicholas; Kramer, Dennis E.; et al.
Background: Preclinical studies suggest that for complete midsubstance anterior cruciate ligament (ACL) injuries, a suture repair of the ACL augmented with a protein implant placed in the gap between the torn ends (bridge-enhanced ACL repair [BEAR]) may be a viable alternative to ACL reconstruction (ACLR). Hypothesis: We hypothesized that patients treated with BEAR would have a noninferior patient-reported outcomes (International Knee Documentation Committee [IKDC] Subjective Score; prespecified noninferiority margin, –11.5 points) and instrumented anteroposterior (AP) knee laxity (prespecified noninferiority margin, +2-mm side-to-side difference) and superior muscle strength at 2 years after surgery when compared with patients who underwent ACLR with autograft. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: One hundred patients (median age, 17 years; median preoperative Marx activity score, 16) with complete midsubstance ACL injuries were enrolled and underwent surgery within 45 days of injury. Patients were randomly assigned to receive either BEAR (n = 65) or autograft ACLR (n = 35 [33 with quadrupled semitendinosus-gracilis and 2 with bone–patellar tendon–bone]). Outcomes—including the IKDC Subjective Score, the side-to-side difference in instrumented AP knee laxity, and muscle strength—were assessed at 2 years by an independent examiner blinded to the procedure. Patients were unblinded after their 2-year visit. Results: In total, 96% of the patients returned for 2-year follow-up. Noninferiority criteria were met for both the IKDC Subjective Score (BEAR, 88.9 points; ACLR, 84.8 points; mean difference, 4.1 points [95% CI, –1.5 to 9.7]) and the side-to-side difference in AP knee laxity (BEAR, 1.61 mm; ACLR, 1.77 mm; mean difference, –0.15 mm [95% CI, –1.48 to 1.17]). The BEAR group had a significantly higher mean hamstring muscle strength index than the ACLR group at 2 years (98.2% vs 63.2%; P < .001). In addition, 14% of the BEAR group and 6% of the ACLR group had a reinjury that required a second ipsilateral ACL surgical procedure ( P = .32). Furthermore, the 8 patients who converted from BEAR to ACLR in the study period and returned for the 2-year postoperative visit had similar primary outcomes to patients who had a single ipsilateral ACL procedure. Conclusion: BEAR resulted in noninferior patient-reported outcomes and AP knee laxity and superior hamstring muscle strength when compared with autograft ACLR at 2-year follow-up in a young and active cohort. These promising results suggest that longer-term studies of this technique are justified. Registration: NCT02664545 (ClinicalTrials.gov identifier)